2002
DOI: 10.1097/00000542-200208000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory Surgery Patients May Be Discharged before Voiding after Short-acting Spinal and Epidural Anesthesia

Abstract: Delay of discharge after outpatient spinal or epidural anesthesia with short-duration drugs for low-risk procedures is not necessary, and may result in prolonged discharge times.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
95
0
6

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(106 citation statements)
references
References 22 publications
5
95
0
6
Order By: Relevance
“…[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] In 41 studies (5,548 patients), urinary retention or PVR with intrathecal anesthesia was assessed (Table 3), 11,13,16,17,20,22, and in 39 studies (4,938 patients), urinary retention or PVR with epidural anesthesia and/or analgesia was assessed (Table 4). 28,33,35,43,[48][49][50]54, An additional five studies involved both intrathecal and epidural techniques. There is overlap in the numbers of patients/studies reported for Tables 2, 3, and 4 because multiple outcomes and/or multiple neuraxial procedures were examined in several studies.…”
Section: Resultsmentioning
confidence: 99%
“…[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] In 41 studies (5,548 patients), urinary retention or PVR with intrathecal anesthesia was assessed (Table 3), 11,13,16,17,20,22, and in 39 studies (4,938 patients), urinary retention or PVR with epidural anesthesia and/or analgesia was assessed (Table 4). 28,33,35,43,[48][49][50]54, An additional five studies involved both intrathecal and epidural techniques. There is overlap in the numbers of patients/studies reported for Tables 2, 3, and 4 because multiple outcomes and/or multiple neuraxial procedures were examined in several studies.…”
Section: Resultsmentioning
confidence: 99%
“…21 The incidence of retention increases with the use of longer-acting intrathecal local anesthetics and hydrophilic neuraxial opioids. 22,23 Local anesthetics block the parasympathetic innervation of the bladder via both the pelvic nerves (S2-S4), which promote detrusor contraction and bladder neck relaxation, and the pudendal nerves (S2-S4), which innervate the external sphincter of the bladder. The sympathetic innervation of the bladder from the spinal cord (between T10 and L2) is also at least partially blocked; this has an inhibitory effect on detrusor activity and an excitatory effect on the bladder neck.…”
Section: Discussionmentioning
confidence: 99%
“…Distension beyond the volume associated with voluntary emptying causes bladder atony and impaired voiding after return of function, and subsequent urinary retention. 33,34 Identified risk factors for postoperative urinary retention are presented in Table IV. [35][36][37][38] In current practice, voiding is not a requirement before discharge from the ASU, as it could delay the discharge of 5%-11% of patients who have no risk factors for urinary retention after ambulatory surgery.…”
Section: Mandatory Voiding Prior To Dischargementioning
confidence: 99%
“…33 In summary, low risk patients can be discharged home without voiding. They should be instructed to return to hospital if they are unable to void within six to eight hours.…”
Section: Mandatory Voiding Prior To Dischargementioning
confidence: 99%